Spherical particles of clay-based antimicrobial particles

By using bipolar antimicrobial particle compositions with specific spherical morphology in viscous flowable compositions, the problem of uneven distribution of bipolar antimicrobial materials is solved, and uniform distribution and effective antimicrobial effects are achieved.

CN119486699APending Publication Date: 2025-02-18UNILEVER IP HLDG BV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380043951.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-24
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, bipolar antimicrobial materials are unevenly distributed in viscous flowable compositions such as toothpaste, resulting in the emergence of enriched areas and low concentration areas and cannot be solved by masking agents.

Method used

Using 30% to 70% by weight of bipolar antimicrobial particle composition, wherein the clay is an asymmetric clay with alternating tetrahedral sheets and octahedral sheets, the quaternary ammonium compound being attached to the coordination cations on the outer surface plane of the clay , and by controlling the spherical degree of the particles between 0.7 and 1.0, ensure uniform suspension of the particles in the liquid composition.

Benefits of technology

A uniform distribution of bipolar antimicrobial particles is achieved, ensuring that the user obtains effective antimicrobial benefits in the personal care composition and improving the visual appearance of the composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161108390000151
    Figure BDA0005161108390000151
  • Figure BDA0005161108390000161
    Figure BDA0005161108390000161
  • Figure BDA0005161108390000181
    Figure BDA0005161108390000181
Patent Text Reader

Abstract

The present invention relates to antimicrobial particles in particulate form and cosmetic and home care compositions comprising such particles. Disclosed is a particulate composition comprising 30 to 70% by weight of bipolar antimicrobial particles, where the antimicrobial particles comprise a clay and a quaternary ammonium compound, where the clay is an asymmetric 1: 1 or 2: 1: 1 type clay having alternating tetrahedral and octahedral sheets, at one outer surface plane, a tetrahedral sheet terminates and at the other outer surface plane, an octahedral sheet, each of said sheets comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordination cation on at least one outer surface plane wherein the particles of the composition are spherical, having a sphericity of 0.7 to 1.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to antimicrobial particles in particulate form and to cosmetic compositions comprising such particles. Background Art

[0002] A variety of cosmetic and home care compositions are known to have a number of end-use benefits through agents including fragrances, antimicrobials and sunscreens.Benefit agents are sometimes encapsulated or granulated to make them, for example, more effective or more stable.

[0003] WO2011036031 A1 (Unilever) discloses a bipolar antimicrobial particle, wherein the precursor is an asymmetric 1:1 or 2:1:1 clay particle having alternating tetrahedral sheets and octahedral sheets, the tetrahedral sheets and octahedral sheets terminating with a tetrahedral sheet at one external surface plane and terminating with an octahedral sheet at another external surface plane, an antimicrobial group is attached to a coordinating cation on one of the external surface planes, the coordinating cation is selected from a quaternary ammonium compound or a quaternary ammonium substance, the quaternary ammonium compound comprises a monoalkyl or alkenyl long chain having an average chain length greater than or equal to C20, the quaternary ammonium substance is selected from cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride, benzethonium chloride, cetrimide, quaternary ammonium salts, polyhexamethylene BH, antimicrobial alcohols, antimicrobial phenols, antimicrobial organic acids / salts, zinc pyridone, ketoconazole, or a combination thereof. The quaternary ammonium compound having antimicrobial properties is immobilized on clay used as a carrier.

[0004] WO 2014 / 102032 A1 (Unilever) discloses a toothpaste comprising the above-mentioned bipolar antimicrobial particles.

[0005] US2012121669 A1 (Colgate-Palmolive) discloses an oral care composition comprising a capsule.

[0006] US2008242767 A1 (Colgate) discloses polymer microcapsules for use in dentifrice. The microcapsules remain intact during the manufacture and storage of toothpaste. The 5 to 50 μm microcapsules are said to have good mechanical properties to withstand shear forces up to about 1000 / s during mixing and high-speed filling; good temperature stability, allowing the capsules to remain intact at temperatures up to about 70°C; good chemical stability, allowing the capsules to be stable in the presence of sodium dodecyl sulfate and pH 5-8. The microcapsules rupture and release CPC directly into the oral cavity without forming inactive complexes.

[0007] KR20040081936 A (Dong A Pharm, 2004) discloses a toothpaste containing CPC particles, i.e., 0.01 to 5 wt% CPC based on the total weight of the composition, wherein CPC is coated on the surface of particles made of precipitated calcium carbonate, silica, zeolite, colloidal silica and anhydrous calcium phosphate. The particles have a particle size of 100 to 750 μm and a strength of 150 to 650 g / cm -2 .

[0008] WO 2021 / 259748 A1 (Unilever) discloses an oral care composition having 0.1 to 10 wt % of bipolar antimicrobial particles and a zinc compound.

[0009] It has been determined that the bipolar antimicrobial materials disclosed in WO2011036031 A1 and WO2014 / 102032 A1 are suitable for use in a variety of home and personal care products, particularly oral care products themselves, but the applicant has observed that when formulated into a viscous flowable composition such as toothpaste typically packaged in a toothpaste tube, the bipolar antimicrobial material is not evenly distributed across the length and width of the packaged composition as might reasonably be expected. There are spatially separated formation zones or regions rich in the material and thereby the antimicrobial material itself, and correspondingly there are regions of lower concentration. Furthermore, at least for clear or water-white formulations, the powder or amorphous form of the bipolar antimicrobial material may cause problems with the visual appearance of the composition. This visual appearance can be corrected by the use of a masking agent, but the uneven distribution or spatial separation problem cannot be solved by any masking agent.

[0010] The standard solution is to use rheological additives to prevent the free movement of the bipolar antimicrobial material, but this is undesirable due to the inevitable effect on the viscosity of such a composition.

[0011] Therefore, there is a risk that the antimicrobial material is not evenly distributed in the bulk of the home or personal care composition. As a result, some users will dispense and obtain an effective portion of the composition, while some other users may not obtain the effective portion and may never know why, while feeling that the portion is effective and a true representation of the bulk of the composition.

[0012] It is an object of the present invention to overcome at least one disadvantage, limitation or drawback of the prior art. Summary of the invention

[0013] A particulate composition comprising 30% to 70% by weight of bipolar antimicrobial particles is disclosed, wherein the antimicrobial particles comprise clay and a quaternary ammonium compound, wherein the clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral and octahedral sheets, terminating with a tetrahedral sheet at one exterior surface plane and with an octahedral sheet at another exterior surface plane, each of the sheets comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordinating cation on at least one exterior surface plane, wherein the particles of the composition are spherical with a sphericity of 0.7 to 1.0.

[0014] According to a second aspect, a liquid personal care composition comprising particles of the granular composition of the first aspect is disclosed.

[0015] When the particulate compositions of the present invention are included in liquid compositions, particularly viscous liquid home care or viscous liquid personal care compositions, the particles remain uniformly suspended in the matrix of the composition, thereby reducing the likelihood of spatial segregation of such particles often observed with such compositions.

[0016] The present inventors have found that when the following bipolar antimicrobial particles are incorporated into a granular composition, wherein the particles of the composition are spherical, having a sphericity of 0.7 to 1.0, it was found that the particles of the granular composition will retain their shape and size when incorporated into a personal care composition. It was surprisingly found that when a granular composition of particles having a specific sphericity according to the present invention is formulated into a personal care composition, it provides a uniform distribution of the antimicrobial particles in the bulk of the personal care composition. This ensures that the user obtains an effective portion of the personal care composition, which portion represents the bulk composition in each dispensing. DETAILED DESCRIPTION OF THE INVENTION

[0018] "Length", "width" and "thickness" refer to the length, width and thickness of a particle or microcapsule in an unaggregated state. The term "length" refers to the average dimension of a particle, usually along the longitudinal axis. The term "width" refers to the average dimension of a particle perpendicular to the length and usually perpendicular to the longitudinal axis. The term "thickness" refers to the average dimension of a particle perpendicular to the length and width. The length, width and thickness can be measured, for example, by scanning electron microscopy (SEM) by averaging the values ​​of at least 10 particles.

[0019] "Sphericity" is a measure of how closely the shape of an object approaches that of a mathematically perfect sphere. The sphericity of a particle is the ratio of the surface area of ​​a sphere (having the same volume as a given particle) to the average surface area of ​​the particle.

[0020] Sphericity can be measured as follows.

[0021] The SEM image of the silica particle sample representing the silica particle sample was magnified 20,000 times, input into the photo imaging software, and the outline of each particle was outlined (two-dimensional). Particles that are close to each other but not attached to each other should be considered as separate particles for this analysis. The outlined particles are then filled with color, and the image is input into a particle characterization software (e.g., IMAGE-PRO PLUS available from Media Cybernetics, Inc., Bethesda, Md.) that can determine the perimeter and area of ​​the particles.

[0022] As used herein, "specific surface area" refers to the specific surface area determined according to the Brunauer-Emmett-Teller method. The value of the specific surface area is measured by satisfying the requirements specified in ASTM Standard D 3663-78.

[0023] Unless otherwise specified, the "particle size" used herein refers to the particle size in the non-aggregated state. For polydisperse samples with particulate matter having a diameter of no greater than 1 μm, the diameter refers to the particle size measured, for example, using dynamic light scattering (see International Standard ISO 13321) using an instrument such as a Zetasizer Nano TM The z-average particle size is measured by Mastersizer (Malvern Instruments Ltd, UK). For polydisperse samples of particulate matter with a diameter greater than 1 μm, the diameter is determined, for example, by laser diffraction using a system meeting the requirements specified in ISO 13320 (e.g., Mastersizer available from Malvern Instruments Ltd). TM The apparent volume median diameter (D50, also called x50 or sometimes d(0.5)) of the particles can be measured using the ELISA (2000) technology.

[0024] The term granular means that the composition of the present invention is in the form of particles. The term granular also means that the composition is neither amorphous nor powdery. Summary of the invention

[0026] The present invention relates to a granular composition comprising 30% to 70% by weight of bipolar antimicrobial particles, wherein the antimicrobial particles comprise clay and a quaternary ammonium compound, wherein the clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral and octahedral sheets, terminating with a tetrahedral sheet at one external surface plane and with an octahedral sheet at another external surface plane, each of said sheets comprising a co-coordinating cation; and the quaternary ammonium compound is attached to the coordinating cation on at least one external surface plane, wherein the particles of the composition are spherical with a sphericity of 0.7 to 1.0.

[0027] The term "granular composition" means that the composition is in granular form.

[0028] Preferably, the particles of the granular composition of the present invention are nearly spherical. However, a certain degree of non-sphericity is not detrimental to its efficacy. The sphericity of the particles is from 0.7 to 1.0, more preferably from 0.75 to 1.0, and even more preferably from 0.8 to 1.0. A sphericity of 1.0 represents a completely spherical particle. Without wishing to be bound by theory, it is believed that the particles are more effective when the sphericity is from 0.7 to 1.0. This is especially true when the particles are used in a viscous personal care composition.

[0029] Preferably, the bulk density of the granular composition is from 0.800 to 0.950 g / cm 3 Further preferably, the average particle size of the particles is 650 μm to 900 μm.

[0030] It is preferred that the particles of the granular composition are friable and have a friability of 0.6 to 0.9 w / w.

[0031] It is particularly preferred that in the compositions of the invention the particles are insoluble in the medium of the composition to which the particle composition is added. In this context, "insoluble" means sufficiently insoluble at ambient temperature that the particles remain insoluble or substantially insoluble in the composition so that their friability under the conditions of use of the composition, and therefore their ability to perform their intended function, is not adversely affected.

[0032] Bipolar antimicrobial particles and clays

[0033] The precursors of the particles with bipolar topological specific characteristics according to the invention are asymmetric 1:1 or 2:1:1 type clay particles with alternating tetrahedral and octahedral sheets, which terminate at the outer surface planes. Particles of 1:1 clay are particularly preferred as precursors.

[0034] Preferably, the 1:1 clay is from the kaolinite or serpentine family of mineral subgroups. Materials included in the kaolinite subgroup include, but are not limited to, kaolinite, dickite, halloysite, and nacrite. Materials in the serpentine subgroup include, but are not limited to, chrysolite, lizardite, and chlorite.

[0035] Preferred 2:1:1 type clays include the chlorite group of minerals. Chlorites include tetrahedron-octahedron-tetrahedron sheets like 2:1 clays, with particularly weakly bonded brucite-like layers between the tetrahedron sheets.

[0036] The tetrahedral sheet preferably includes coordinating tetrahedral cations of silicon. The tetrahedral sheet may also include isomorphously substituted coordinating tetrahedral cations that are not silicon. Isomorphously substituted coordinating tetrahedral cations include, but are not limited to, cations of aluminum, iron or boron.

[0037] The octahedral sheet preferably comprises coordinating octahedral cations of aluminum. The octahedral sheet may also comprise isomorphously substituted coordinating octahedral cations other than aluminum. Isomorphously substituted coordinating octahedral cations include cations of magnesium or iron.

[0038] Preferably, the antimicrobial quaternary ammonium compound is attached to a coordinating cation on the outside of an outer surface plane. Thus, the antimicrobial molecule is attached to a coordinating cation on the outside of a tetrahedral sheet. Alternatively, the antimicrobial molecule is attached to a coordinating cation on the outside of an octahedral sheet. According to another aspect, the coordinating cation on the outside of each of the tetrahedral and octahedral surface sheets is attached to the antimicrobial molecule, provided that the antimicrobial molecule attached to the coordinating cation on the outside of the tetrahedral surface sheet is not the same as the molecule attached to the coordinating cation on the outside of the octahedral surface sheet. The antimicrobial molecule is preferably attached to the coordinating cation on the outer surface of the octahedral surface plane, and is not preferably attached to the coordinating cation of a non-external tetrahedral or octahedral plane or on the inside of the surface sheet.

[0039] Preferably, in the antimicrobial material, the antimicrobial agent is attached to coordinating cations on the outer surfaces of the octahedral surface planes.

[0040] In the granular composition of the present invention, it is preferred that the bipolar antimicrobial particles comprise 0.5 to 5 parts by weight of the quaternary ammonium compound and 90 to 98 parts by weight of the clay, on a w / w basis.

[0041] Preferred quaternary ammonium compounds are cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride (BKC), benzethonium chloride, cetrimonium bromide, quaternary ammonium salts, tetrabutylammonium bromide, undecylenamidopropyltrimethylammonium methylsulfate, methylbenzethonium chloride, cetethyldimonium bromide, cetromonium tosylate, cocotrimethylammonium chloride, dodecylbenzyltrimethylammonium chloride, laurylisoquinolinium bromide, laurylpyridinium chloride, dequalinium chloride or domiphene.

[0042] A particularly preferred antimicrobial agent is cetylpyridinium chloride (CPC). Without being bound by theory, it is believed that the primary activity is associated with the cationic charge of its amine group. Thus, cetylpyridinium chloride is attracted to and binds to negatively charged protein moieties on the cell membrane or cell wall of microorganisms and to surfaces such as teeth that are also generally negatively charged. The resulting attachment to the microorganism disrupts the cell wall structure, leading to leakage of intracellular fluids and ultimately killing the associated microorganism.

[0043] It is particularly preferred that the clay precursor is a 1:1 clay particle. It is further preferred that the clay precursor is kaolinite. It is particularly preferred that the quaternary ammonium compound is cetylpyridinium chloride. It is further particularly preferred that when the clay precursor is kaolinite, the antimicrobial quaternary ammonium compound is cetylpyridinium chloride.

[0044] Method for preparing bipolar antimicrobial particles

[0045] Any chemical reaction or series of reactions in which the antimicrobial quaternary ammonium compound is selectively attached to the coordinating cations on the external planes of the tetrahedral or octahedral surface planes of the asymmetric clay can be used to prepare the bipolar antimicrobial particles. In order to obtain true bipolar antimicrobial particles, it is preferred that the reaction is selective for only one of the external planes. Selectivity means that more than 50% of the total antimicrobial molecules are present on one external plane, preferably more than 75%, more preferably more than 80%, still more preferably more than 90%, even more preferably more than 95%, or even more than 99%. Therefore, the following chemical reaction or series of reactions in which the same antimicrobial molecule is attached to the coordinating cations of two surface sheets (i.e., the octahedral sheet and the tetrahedral sheet) is not preferred.

[0046] The particle with bipolar properties may have two distinct regions on its surface with different surface properties. It is particularly preferred that the particle has two spatially distinct outer surfaces with different surface characteristics. It is envisaged that various types of anisotropic properties may be imparted to the surface of the particle with bipolar properties by selecting specific antimicrobial molecules with specific groups and selectively attaching them to the coordinating cations of the tetrahedral and / or octahedral surface sheets.

[0047] The method comprises the steps of contacting the precursor with an inorganic acid, adding an antimicrobial quaternary ammonium compound to the mixture, adjusting the pH of the solution to above 8, heating the mixture to a temperature of 50 to 150° C. for about 30 minutes to 10 hours while stirring, and isolating a solid product comprising a bipolar particulate antimicrobial agent. When the application temperature is greater than 100° C., a pressure vessel is preferred.

[0048] The raw clay is preferably first treated with a mineral acid, preferably hydrochloric acid. The hydrochloric acid is used in a concentration range of 0.01 N to 1 N, preferably about 0.1 N. The clay particles and the acid are then stirred. Stirring is typically performed for 10 to 60 minutes, preferably about 30 minutes.

[0049] After the precursor is treated with the mineral acid for about 30 minutes, the pH of the system is preferably adjusted to above 8 by adding 0.1 (M) NaOH to the solution.

[0050] The desired antimicrobial molecule is preferably added to the dispersion after the clay has been treated with hydrochloric acid.The antimicrobial molecule is then added at a concentration of 0.001 to 30%, preferably 0.01 to 5%, based on the total weight of the dispersion.

[0051] After adding the antimicrobial molecules and adjusting the pH of the dispersion, the solution is heated at 50°C to 150°C, preferably 70°C to 90°C, more preferably 80°C, preferably with stirring for 1 to 10 hours, preferably 4 to 8 hours, more preferably about 6 hours. The solid product comprising the bipolar particulate antimicrobial agent is isolated.

[0052] After the reaction, the dispersion mixture is preferably centrifuged to obtain the bipolar antimicrobial particles as a residue. It is then preferably washed with a large amount of water and subsequently with a ketone solvent (e.g. acetone). It is then dried in an oven to obtain the final product.

[0053] In this reaction, the antimicrobial quaternary ammonium compound is preferably attached to the coordinating cations of the octahedral sheet by covalent bonds.The antimicrobial particles prepared by this method have different wettability characteristics for the two outer surface planes.

[0054] Preferably, the quaternary ammonium compound is selected from cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride (BKC), benzethonium chloride, cetrimonium bromide, quaternary ammonium salts, tetrabutylammonium bromide, undecylenamidopropyltrimethylammonium methylsulfate, methylbenzethonium chloride, cetyldimethylethylammonium bromide, cetrimonium p-toluenesulfonate, cocotrimethylammonium chloride, dodecylbenzyltrimethylammonium chloride, laurylisoquinolinium bromide, laurylpyridinium chloride, dequalinium chloride or domiphene.

[0055] A particularly preferred antimicrobial quaternary ammonium compound is cetylpyridinium chloride (CPC). It is believed that the primary activity is associated with the cationic charge of its amine group. Thus, cetylpyridinium chloride is attracted to and binds to negatively charged protein moieties on the cell membrane or cell wall of microorganisms and to surfaces that are also generally negatively charged, such as tooth surfaces. The resulting attachment to microorganisms disrupts the cell wall structure, leading to leakage of intracellular fluids and ultimately killing the associated microorganisms.

[0056] It is particularly preferred that the precursor of the clay is a 1:1 clay particle. It is further preferred that the precursor of the clay is kaolinite. It is particularly preferred that the antimicrobial quaternary ammonium compound is cetylpyridinium chloride. It is further particularly preferred that when the precursor of the clay is kaolinite, the antimicrobial quaternary ammonium compound is cetylpyridinium chloride.

[0057] It is preferred that the median particle size (D50) of the bipolar antimicrobial particles is from 0.1 to 10 μm, more preferably from 0.4 to 1 μm, and most preferably from 0.5 to 0.8 μm. Lower particle sizes also provide an effective mechanism for increasing the antimicrobial loading if desired. The particle size distribution (D50), also known as the median diameter or median of the particle size distribution, is the particle size value at 50% in the cumulative distribution. For example, if the D50 is 5.8 μm, 50% of the particles in the sample are larger than 5.8 μm and 50% are smaller than 5.8 μm. D50 is generally used to indicate the particle size of a group of particles. D50 is the size in microns that separates the distribution above and below the diameter.

[0058] Lower particle sizes also provide an effective mechanism for increasing the antimicrobial quaternary ammonium compound loading, if desired. Particle size distribution (D50), also known as the median diameter or median of the particle size distribution, is the particle size value at 50% in the cumulative distribution. For example, if the D50 is 5.8 μm, 50% of the particles in the sample are larger than 5.8 μm and 50% are smaller than 5.8 μm. D50 is often used to represent the particle size of a group of particles. D50 is the size in microns that divides the distribution above and below half of the diameter.

[0059] Size and Sphericity

[0060] The particles of the composition are spherical, having a sphericity of 0.7 to 1.0. However, a certain degree of non-sphericity is not detrimental to the performance of the particle composition. More preferably, the sphericity is 0.75 to 1.0, and even more preferably 0.8 to 1.0. A sphericity of 1.0 represents a perfectly spherical particle. Without wishing to be bound by theory, it is believed that when the sphericity is 0.7 to 1.0, the particles are more effective than when outside this range. This is especially true when the particles are used in viscous liquid home care and personal care compositions.

[0061] Preferably, the bulk density of the granular composition is from 0.800 to 0.950 g / cm 3 Further preferably, the average particle size of the particles is 650 to 900 μm.

[0062] It is preferred that the particles of the granular composition are friable, having a friability of 0.6-0.9 w / w. In particularly preferred compositions of the invention, the particles should be insoluble in the medium of the composition into which they are incorporated. In this context, "insoluble" means having sufficient insolubility at ambient temperature such that the particles remain insoluble or substantially insoluble in the composition such that their friability, and therefore their ability to perform their intended function, under the conditions of use of the composition is not adversely affected.

[0063] Binder

[0064] The granular composition of the present invention preferably comprises from 10% to 40% by weight of a water-insoluble binder.

[0065] As used herein, "binder" refers to a material used to bind two or more other materials in a particle together. Preferably, the binder is a carbohydrate. Preferably, the carbohydrate is starch, more preferably corn starch. When the water-insoluble binder is starch, preferably the amount of starch in the composition is 10 wt % to 20 wt %, still more preferably 10 wt % to 19 wt %, further more preferably 10 wt % to 18 wt %. The binder according to the present invention is a carbohydrate that is not cellulose or cellulose derivatives.

[0066] Preferably, the granular composition comprises 10 to 40 wt% of a water-insoluble binder, more preferably 10 to 30 wt% of a water-insoluble binder. Preferably, the granular composition comprises at least 11 wt%, more preferably at least 12 wt%, more preferably at least 13 wt%, most preferably at least 15 wt% of a water-insoluble binder, but typically no more than 35 wt%, more preferably no more than 30 wt%, more preferably no more than 28 wt%, more preferably no more than 27 wt%, most preferably no more than 25 wt%, more preferably no more than 20 wt% of a binder, based on the weight of the granular composition.

[0067] Preferably, when the granular composition comprises starch as a binder, it is preferred that the composition comprises from 10 wt% to 20 wt% starch.

[0068] Coating agent:

[0069] The granular composition of the present invention preferably comprises 5% to 23% by weight of a water-insoluble coating agent. Preferably, the coating agent is selected from [meth]acrylates, aminoalkyl [meth]acrylates, cellulose or cellulose derivatives or mixtures thereof. The coating agent may also be used as a spheroidizing agent. An example of a spheroidizing agent in the composition of the present invention is preferably microcrystalline cellulose. Preferably, the coating agent is based on [meth]acrylate. Preferably, the [meth]acrylate-based coating agent is a latex dispersion of a neutral polymer produced by emulsion polymerization of, for example, ethyl acrylate and methyl methacrylate. Commercially available coating agents include Eudragit NE 30D and Eudragit NM 30D, which are coating systems based on polymethacrylates. The difference between Eudragit NE 30D and Eudragit NM 30D is the content and nature of the emulsifier.

[0070] It is also preferred that the coating agent is cellulose or a cellulose derivative. Preferably, the coating agent is fibrous cellulose. More preferably, the binder is an alkyl cellulose, and even more preferably, the alkyl cellulose is ethyl cellulose. As used herein, ethyl cellulose polymer refers to a cellulose derivative in which some of the hydroxyl groups on the repeating glucose units are converted to ether groups. Preferably, the coating agent can be in any form, including but not limited to solid, liquid dispersion, more preferably aqueous dispersion, or mixtures thereof.

[0071] Preferably, when the coating agent is cellulose or a cellulose derivative, the amount of cellulose or a cellulose derivative is preferably from 5% to 11% by weight, still more preferably from 5% to 10.5% by weight. Without wishing to be bound by theory, the inventors believe that when the amount of cellulose or a cellulose derivative in the granular composition is above 11% by weight, it causes the granular composition to swell in the presence of water, in particular when the granular composition according to the present invention is incorporated into an oral care composition. This expansion over time has a negative impact on the size and shape of the granular composition during storage.

[0072] Preferably, the coating agent has a low glass transition temperature, more preferably, the glass transition temperature is below 132°C, more preferably between 40°C and 50°C.

[0073] When both the binder and the coating agent are based on [meth]acrylate polymers, they are preferably different.

[0074] Preferably, the granular composition comprises 5 to 23 wt% of coating agent, more preferably 5 to 15 wt% of coating agent. Preferably, the granular composition comprises at least 6 wt%, more preferably at least 8 wt%, more preferably at least 9 wt%, most preferably at least 10 wt% of coating agent, but typically no more than 19 wt%, more preferably no more than 18 wt%, still more preferably no more than 17 wt%, still more preferably no more than 16 wt%, most preferably no more than 15 wt% of coating agent, based on the weight of the granular composition.

[0075] It is further preferred that the granular composition of the present invention comprises at least one of a granulation aid or a spheroidization aid.

[0076] Method for preparing granular composition:

[0077] According to another aspect of the present invention, a method of preparing the granular composition according to the first aspect is disclosed.

[0078] A method for preparing a granular composition according to the first aspect of the present invention, the method comprising the following steps:

[0079] (i) mixing bipolar antimicrobial particles, a water insoluble binder, and a water insoluble coating agent to form a mixture;

[0080] (ii) extruding the mixture to form an extrudate;

[0081] (iii) spheronizing the extrudate to form the granular composition,

[0082] The particles of the composition are spherical, having a sphericity of 0.7 to 1.0.

[0083] According to a second aspect, a method for preparing a granular composition comprises the step of mixing the bipolar antimicrobial particles, the water-insoluble binder and the water-insoluble coating agent to form a homogeneous mixture. Preferably, the mixing is carried out in a mixer. Preferably, the mixer can be any mixer known to those skilled in the art for granulation. Preferably, the ingredients are mixed in a mixer to form a wet mass having a desired consistency.

[0084] The wet mass is then preferably extruded through a die slot of an extruder and the extrudate emerging from the die slot is cut. Preferably the wet mass is extruded by, for example, a screw-type extruder. Although the die slot and thus the extrudate may take any suitable shape, a spaghetti or noodle shape is more preferred. When the extrudate takes the form of spaghetti or noodles, the extruder die hole diameter is preferably in the range of about 0.1 mm to about 1 mm, more preferably 0.4 to 0.8 mm. The extrudate is preferably cut using a high speed cutting unit after passing through the die plate of the extruder.

[0085] Once the extrudate is converted into a plurality of smaller sized pellets, the next step involves spheronizing the extrudate in a spheronizer to give the pellets a spherical shape. Spheronizers typically deform the pellets through a combination of mechanical force and optionally heat. When heat is applied to the pellets being spheronized, it is preferred that the temperature be at least 1 to 5 degrees above the Tg or melting point of the largest amount of thermoforming material in the pellets.

[0086] Preferably after spheronization, the spheronized extrudate is dried and then preferably sieved to provide a granular composition according to the present invention. Preferably, the drying step is carried out at a temperature of 40° C. to 60° C. Extrusion / spheronization is a process in which the active ingredient and excipients are sequentially mixed, wet granulated, extruded and spheronized to form granules.

[0087] Personal care compositions

[0088] The present invention also relates to a liquid personal care composition comprising the granular composition of the present invention. Preferably, the personal care composition is a leave-on skin lotion, skin cream, antiperspirant, deodorant, serum, shampoo, hair conditioner, hair serum, hair spray, dentifrice, hand soap, shower gel, shower gel or soap.

[0089] Preferably the liquid personal care composition is a dentifrice. Preferably the dentifrice is a toothpaste. More preferably the toothpaste is a gel. Typically such a toothpaste is transparent. Preferably when the dentifrice is a toothpaste, the toothpaste comprises at least one of a calcium-based abrasive or a silica-based abrasive, more preferably a silica-based abrasive. Preferably the silica abrasive is precipitated silica. Suitable precipitated silica for use as abrasive amorphous silica particles in the present invention are commercially available and include those sold by PQ Corporation under the trade name AC43, AC77, AC35 and Those sold as AC 33. Mixtures of any of the materials mentioned may also be used. Preferably the toothpaste composition comprises from 1 to 10 wt% silica abrasive.

[0090] Alternatively, the toothpaste includes a calcium-based abrasive. A particularly preferred abrasive is finely ground natural chalk (FGNC). FGNC is obtained from limestone or marble. FGNC can also be chemically or physically modified by coating during or after the grinding process by heat treatment. Typical coating materials include magnesium stearate and magnesium oleate. The morphology of FGNC can also be changed during the grinding process by using different grinding techniques, such as ball milling, air flow classification grinding or spiral jet grinding. FGNC can be used as the only calcium-containing abrasive. However, FGNC can also be used with other calcium-containing abrasives to balance wear. Other preferred calcium-containing abrasives include dicalcium phosphate (DCP), calcium pyrophosphate and precipitated calcium carbonate (PCC). When a combination of calcium-containing abrasives is used, it is preferred that FGNC is 35 to 100% of the total abrasive, more preferably 75 to 100%, especially 95 to 100%. In this case, the balance is most preferably PCC.

[0091] Preferably, the toothpaste comprises 40 to 85 wt % of a liquid continuous phase based on the total weight of the dentifrice. Such a liquid continuous phase generally comprises a mixture of water and a polyol in various relative amounts, wherein the amount of water is generally 10 to 45 wt % (based on the total weight of the dentifrice) and the amount of the polyol is generally 30 to 70 wt % (based on the total weight of the dentifrice).

[0092] Humectants are often included in toothpaste for a soft, delicate mouthfeel. Humectants also reduce the tendency of toothpaste to lose moisture. Preferred toothpaste compositions contain 3.5% to 40% by weight of humectants. Further preferred compositions have 10% to 40% by weight, more particularly 10% to 20% by weight of humectants. A particularly preferred humectant is sorbitol, which is typically obtained as a 70% aqueous solution. Other preferred humectants include glycerol, maltitol, and xylitol. For a lubricated mouthfeel, more preferred toothpastes contain glycerol and sorbitol, but their cumulative content should not exceed the disclosed upper limit. Lower humectant content provides an effective way to reduce product costs.

[0093] Preferably, the toothpaste comprises 0.5 to 10% by weight of a binder or thickener, based on the total weight of the dentifrice. Suitable binders or thickeners include carboxyvinyl polymers (e.g., polyacrylic acid crosslinked with polyallyl sucrose or polyallyl pentaerythritol), hydroxyethyl cellulose, hydroxypropyl cellulose, water-soluble salts of cellulose ethers (e.g., sodium carboxymethyl cellulose and sodium carboxymethyl hydroxyethyl cellulose), natural gums (e.g., carrageenan, karaya gum, guar gum, xanthan gum, gum arabic and tragacanth), finely divided silica, hectorite, colloidal magnesium aluminum silicate, and mixtures thereof.

[0094] It is further preferred that the toothpaste of the present invention comprises 0.2 to 10% by weight of a surfactant based on the total weight of the dentifrice. Suitable surfactants include anionic surfactants such as sodium, magnesium, ammonium or ethanolamine salts of C8 to C18 alkyl sulfates (e.g. sodium lauryl sulfate), C8 to C18 alkyl sulfosuccinates (e.g. sodium dioctyl sulfosuccinate), C8 to C18 alkyl sulfoacetates (e.g. sodium lauryl sulfoacetate), C8 to C18 alkyl sarcosinates (e.g. sodium lauryl sarcosinate), C8 to C18 alkyl phosphates (which may optionally include up to 10 ethylene oxide and / or propylene oxide units) and sulfated monoglycerides. Other suitable surfactants include nonionic surfactants such as optionally polyethoxylated fatty acid sorbitan esters, ethoxylated fatty acids, esters of polyethylene glycol, ethoxylates of fatty acid monoglycerides and diglycerides, and ethylene oxide / propylene oxide block polymers. Other suitable surfactants include amphoteric surfactants such as betaines or sultaines.

[0095] Further preferably, the toothpaste comprises a montmorillonite clay in addition to the clay present via the bipolar antimicrobial particles. Montmorillonites constitute a group of natural aluminosilicate minerals known as phyllosilicates or layered silicates. Preferred montmorillonite clays are selected from montmorillonites (bentonites, hectorites and their derivatives); purified magnesium aluminum silicates (various grades available as VEEGUM (R) commercially available from RT Vanderbilt Company); purified sodium magnesium silicate (available in various grades as LAPONITE (R) commercially available); organically modified montmorillonites, including tetraalkyl and / or trialkyl ammonium montmorillonites (organically modified montmorillonite clays), such as quaternium-18 bentonite, quaternium-18 hectorite, stearalkonium bentonite and stearalkonium hectorite and mixtures thereof. Particularly preferred are magnesium aluminum silicate clays. Examples are VEEGUM (R)HV. The clay tends to swell when exposed to water. Preferred toothpaste compositions contain 0.2 to 3 wt% clay. More preferred compositions contain 0.5 to 1 wt% clay.

[0096] It is believed that montmorillonite clay plays a role not only in the sensory profile, but also in thickening the composition.

[0097] More preferably, the toothpaste comprises a zinc salt, preferably zinc sulphate or zinc chloride, more preferably zinc sulphate heptahydrate.Preferably, the zinc salt is present in an amount of 0.05 to 1.0 wt %, more preferably 0.1 to 0.5 wt % of the total composition.

[0098] The composition of the present invention may include a preservative, preferably sodium benzoate. Preferably, the preservative is present in an amount of 0.1 to 1% by weight of the total composition. Preferably, the pH of the composition at 20°C is 4 to 10, more preferably 7 to 9.

[0099] The composition of the present invention may also include a deposition aid. In the context of the present invention, the term "deposition aid" generally refers to a material that further aids the deposition of the brightener from the composition. An example is polystyrene sulfonate. Another example is polymer.

[0100] The dentifrice composition may also include other optional ingredients conventional in the art, such as fluoride ion sources, anticalculus agents, buffering agents, flavoring agents, sweeteners, coloring agents, opacifiers, preservatives, anti-sensitivity agents, and antimicrobial agents.

[0101] Preferably, the personal care composition comprises from 0.1 wt% to 3 wt% of the granular composition according to the present invention, still more preferably, the personal care composition comprises from 1 wt% to 2.5 wt% of the granular composition.

[0102] Various examples are given below that illustrate the present invention, which in no way should be considered to limit the scope of the invention.The present invention will now be explained with the aid of the following non-limiting examples. DETAILED DESCRIPTION

[0103] Example

[0104] Example 1: Preparation of antimicrobial particles (CPC-clay)

[0105] 5 grams of kaolinite were placed in 500 ml of 0.1N HCl solution and ultrasonicated for 30 minutes. The pH was then increased to 9 by dropping sodium hydroxide solution. 10 g of CPC (cetylpyridinium chloride) was added thereto and the suspension was stirred on a magnetic stirrer for 6 hours while maintaining the temperature of the solution at 75 to 80°C. The suspension was then washed with water for about 10 times to remove excess CPC and a final ethanol wash was performed. The clay was then dried in a hot air oven. The composition prepared as above contained 97.5% by weight of kaolinite and 2.5% by weight of cetylpyridinium chloride. The D50 of the particles was 0.5 μm.

[0106] Example 2

[0107] In this experiment, the bipolar antimicrobial particles of Example 1 were granulated as briefly described below.

[0108] All raw materials were weighed according to the requirements of the relevant formula.

[0109] Excipients (if any) are blended and mixed thoroughly in a planetary mixer at low rpm for 2 to 5 minutes. A small amount of granulation fluid is then added to the dry blend and mixed thoroughly. This process step is repeated until a wet mass of the desired consistency is obtained. The wet mass is then extruded at a speed of 50 rpm using a 0.8 mm die. The extrudate is spheronized, ensuring a balance between spheronization speed, time, and spheronizer plate size. The resulting pellets are dried at 60° C. until all pellets are completely dry. The pellets are sieved to obtain particles within a defined size range.

[0110] Example 3: Comparative Example

[0111] Granules of different compositions were prepared for comparative analysis. The details of the compositions are shown in Table 1. All granule compositions of Table 1 are comparative examples, i.e., not within the scope of the present invention.

[0112] Table 1

[0113]

[0114] Observations:

[0115] A to D: The particles were unstable when included in a standard gel toothpaste.

[0116] E: Medium-hard spherical noodles

[0117] F: Long string noodles - particles curled during spherification

[0118] G: Powder particles

[0119] H: Unformed particles

[0120] I: Rod-shaped pellets formed

[0121] When a series of gel toothpaste compositions (A1 to I1) were prepared using the granules / sticks / noodles of Table 1, it was observed that the granules / sticks / noodles were unstable and lost their shape and structure during short-term storage (10-15 days). Therefore, none of the above compositions are suitable for incorporation into gel toothpaste compositions. The basic composition of gel toothpaste is detailed in Table 4.

[0122] Example 4

[0123] The purpose of this experiment was also to prepare granules, but all granule compositions of Table 2 are within the scope of the present invention.

[0124] Table 2

[0125]

[0126] In the granule compositions provided in Table 2, CPC-clay is the bipolar antimicrobial particle, corn starch is the water-insoluble binder, MCC, Eudragit NM 30D, Eudragit RSPO, Ethylcellulose Dispersion Type B NF, Eudragit NE40D (40% w / w), Ethylcellulose (Ethocel Standard 45) are used as water-insoluble coating agents.

[0127] In each case, the particles were formed at 1400 rpm for 20 minutes. In the particle compositions of 1, 3, 4, 7 and 8, the particles were spherical, and their shape was maintained even after 5 days. It was found that compositions 2, 5 and 6 with only a coating agent and no binder provided non-spherical particle compositions. The physical properties of compositions 7 and 8 are listed in Table 3 below. The particles of 7 and 8 were further tested according to Example 3.

[0128] Table 3

[0129] performance Composition 7 Composition 8 Bulk density <![CDATA[0.893g / cm 3 ]]> 0.8771g / ml friability 0.70%w / w 0.66%w / w Particle size distribution --- --- 1180μ 0.3% 1180μ 1003μ 8.0% 1003μ 850μ 61.7% 850μ 710μ 22.45% 710μ 600μ 0.70% 600μ 250μ&fine powder 6.67% 250μ&fine powder Sphericity 0.8 0.8

[0130] Example 5: Gel toothpaste composition

[0131] All the granular compositions of Table 2 were used to prepare standard gel toothpaste formulations numbered 1A to 8A (1A contained granular composition 1 of Table 2, and so on). The detailed formula of the toothpaste is shown in Table 4.

[0132] Table 4

[0133] Element Wt% Sorbitol (70%) 58.0 Thickening Silica 8.5 Silica Abrasive (Medium) 9.0 Silica Abrasive (High) 1.6 SLS 2.7 Particles** 2.5 SCMC 9H 0.7 NaOH solution (10%) 0.3 Water and others 100.0

[0134] **Reference Example 2

[0135] Considering that the toothpaste comprises 2.5 wt% of the granular composition, the wt% of the antimicrobial agent (quaternary ammonium compound, CPC) is estimated to be 0.04% (in the toothpaste composition).

[0136] Example 6

[0137] Two selected toothpaste compositions (7A and 8A) of Table 4 were selected for further experiments. In this case, each toothpaste composition 7A and 8A was packaged in a different toothpaste tube, thereby obtaining a total of 100 tubes (200 ml each) of toothpaste according to composition 7A and another 100 tubes (200 ml each) of toothpaste according to 8A.

[0138] In each group of 100 tubes, 5 tubes are randomly selected for testing. Therefore, there are now two groups of tubes, each consisting of 5 tubes. The toothpaste samples are drawn from each tube as follows:

[0139] - Three samples from the top section

[0140] - Three samples from the middle section

[0141] - Three samples from the bottom section

[0142] Each sample was tested for CPC (cetylpyridinium chloride) content (present in the granules). The expected amount of CPC is 0.04% by weight of the toothpaste composition. The following observations were recorded.

[0143] Table 5

[0144]

[0145] The data in Table 5 show that the observed values ​​of CPC are nearly constant in all three regions of the tube, indicating that there are no significant differences between the middle, top, and bottom layers of the composition (as in the package), and that the observed values ​​do not deviate much from the calculated or expected value of 0.04 wt % (in the toothpaste). In other words, there is no spatial segregation into regions of high or low concentration of particles (and thus antimicrobial agent).

[0146] This indicates that when the granular compositions of the present invention having bipolar antimicrobial particles and a sphericity of 0.7 to 1.0 are incorporated into personal care compositions (toothpastes), consumers receive the same amount of antimicrobial benefits in each dispensing. In addition, these granular compositions can also be visually perceived in the form of granules, and the granular compositions further enhance the overall appearance of the toothpaste (personal care composition) while delivering functional benefits.

Claims

1. A granular composition comprising 30% to 70% by weight of bipolar antimicrobial particles, wherein the antimicrobial particles comprise clay and a quaternary ammonium compound, wherein the clay is an asymmetric 1:1 or 2:1:1 type clay having alternating tetrahedral and octahedral sheets, terminating with a tetrahedral sheet at one exterior surface plane and terminating with an octahedral sheet at another exterior surface plane, each of said sheets comprising a coordinating cation; and the quaternary ammonium compound is attached to the coordinating cation on at least one exterior surface plane, wherein the particles of the composition are spherical with a sphericity of 0.7 to 1.

0.

2. The composition of claim 1, wherein the particles have an average particle size of 650 to 900 μm.

3. The composition of claim 1 or 2, wherein the bulk density of the granular composition is 0.800 g / cm 3 Up to 0.950g / cm 3 .

4. The composition of any one of claims 1 to 3, wherein the particles are friable and have a friability of 0.6-0.9 w / w.

5. The composition of any one of claims 1 to 4, wherein the composition comprises: a) 10-40 wt % of a water-insoluble binder; and, b) 5-23% by weight of a water-insoluble coating agent.

6. The composition of any one of claims 1 to 5, wherein the quaternary ammonium compound is selected from cetylpyridinium chloride (CPC), cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), benzalkonium chloride (BKC), benzethonium chloride, cetrimonium bromide, quaternary ammonium salts, tetrabutylammonium bromide, undecylenamidopropyltrimethylammonium methylsulfate, methylbenzethonium chloride, cetyldimethylethylammonium bromide, cetrimonium toluenesulfonate, cocotrimethylammonium chloride, dodecylbenzyltrimethylammonium chloride, laurylisoquinolinium bromide, laurylpyridinium chloride, dequalinium chloride or domiphene.

7. A composition as claimed in any one of claims 1 to 6, wherein the antimicrobial agent is attached to the coordinating cations on the outer surface of the octahedral surface planes.

8. The composition of any one of claims 1 to 7, wherein the water-insoluble binder is a carbohydrate, wherein the carbohydrate is not cellulose or a cellulose derivative.

9. The composition according to any one of claims 1 to 8, wherein the water-insoluble coating agent is a polymer selected from [meth]acrylates, cellulose, or a derivative of cellulose, or a mixture thereof.

10. A granular composition as claimed in any one of claims 1 to 9, wherein the bipolar antimicrobial particle comprises 0.5 to 5 parts by weight of the quaternary ammonium compound and 90 to 98 parts by weight of the clay on a w / w basis.

11. A particle composition as claimed in any one of claims 1 to 10, wherein when the clay is an asymmetric 1:1 clay, it belongs to the kaolinite or serpentine group of minerals.

12. A granular composition as claimed in any one of claims 1 to 11, wherein when the clay is an asymmetric 2:1 clay, it belongs to the chlorite group of minerals.

13. A liquid personal care composition comprising particles of the granular composition of any one of claim 12.

14. The personal care composition of claim 13, wherein the personal care composition is a leave-on skin lotion, a skin cream, an antiperspirant, a deodorant, a serum, a shampoo, a hair conditioner, a hair serum, a hair spray, a dentifrice, an oral care composition, a hand wash, a body wash, a shower gel, or a soap.

15. The personal care composition of claim 14, wherein the dentifrice is a toothpaste composition.

Citation Information

Patent Citations

  • Dental composition for antiplaque and antigingivity

    KR1020040081936A

  • Polymeric Encapsulates Having a Quaternary Ammonium Salt and Methods for Producing the Same

    US20080242767A1

  • Oral care composition comprising capsules

    US20120121669A1

  • An antimicrobial particle and a process for preparing the same

    WO2011036031A1

  • Oral care composition having an adduct of clay and antibacterial agent

    WO2014102032A1